1998
DOI: 10.1143/jjap.37.1768
|View full text |Cite
|
Sign up to set email alerts
|

Ohmic Contact to P-Type GaN

Abstract: Investigations of the new metal scheme for ohmic contact to p-GaN have been carried out. The specific contact resistance was measured to be ρc=3.6×10-3 Ω cm2 which is the lowest value ever reported for moderately doped p-GaN (4.4×1017/cm3). All metals were deposited on metalorganic chemical vapour deposition (MOCVD) grown p-GaN. The interaction mechanism between Ni and p-GaN has been investigated. Zn diffusion has been observed during annealing in Au–Zn/Ni on p-GaN. The interfacial reaction mechanism during an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 15 publications
1
24
0
1
Order By: Relevance
“…The shift of the surface Fermi level could be associated with the formation of interfacial gallide phase, causing deep acceptor-like Ga vacancies to be generated near the GaN surface. 6 Furthermore, the in-diffusion of Zn into GaN might also contribute to the increase of carrier concentration, as suggested by Youn et al 17 However, further investigation is required to confirm this point. Second, this could be related to the formation of p-type Ni oxide, as noted from the Ni 2p core level behaviors ͑not shown͒.…”
Section: Low-resistance and Transparent Ohmic Contacts To P-type Gan mentioning
confidence: 88%
See 1 more Smart Citation
“…The shift of the surface Fermi level could be associated with the formation of interfacial gallide phase, causing deep acceptor-like Ga vacancies to be generated near the GaN surface. 6 Furthermore, the in-diffusion of Zn into GaN might also contribute to the increase of carrier concentration, as suggested by Youn et al 17 However, further investigation is required to confirm this point. Second, this could be related to the formation of p-type Ni oxide, as noted from the Ni 2p core level behaviors ͑not shown͒.…”
Section: Low-resistance and Transparent Ohmic Contacts To P-type Gan mentioning
confidence: 88%
“…16 Recently, in an effort to increase carrier concentration near the surface region of p-GaN, group II elements, such as Zn and Be, were intentionally added to a Au layer in direct contact to p-GaN. 17,18 It was shown that such schemes could be effective in increasing carrier concentration near the surface region. Very recently, expecting a similar doping effect, Song, Leem, and Seong 19 employed Ni-Mg solid solution to obtain low resistivity ohmic contacts to p-GaN.…”
Section: Low-resistance and Transparent Ohmic Contacts To P-type Gan mentioning
confidence: 99%
“…Numerous papers have dealt with improving the ohmic properties of the contacts to p-GaN by increasing the charge carrier concentration in the surface region of pGaN by means of group II dopants incorporated into the metallization layer [2][3][4][5][6][7]. In the case of light emitting devices (diodes, lasers), when the ohmic contacts have to be also sufficiently transparent for visible light, this requirement has been satisfied by using very thin metallic contact layers on p-GaN.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous procedures have been used to improve the ohmic properties of the contacts to p-GaN by increasing the charge carrier concentration in the surface region of p-GaN by means of group II dopants incorporated into the metallization layer [3][4][5][6][7][8]. For improving the optical transparency of the contacts, metallization structures based on ZnO have been used.…”
Section: Introductionmentioning
confidence: 99%